2020
DOI: 10.1111/dmj.12057
|View full text |Cite
|
Sign up to set email alerts
|

Product–Service Systems Applied to Reusable Packaging Systems: A Strategic Design Tool

Abstract: Environmental sustainability is under the threat of excessive single‐use plastic packaging waste, which current waste management fails to address. Therefore, the issue has led to an identification of the solution that can curb packaging waste without sacrificing social needs.Reusable packaging systems (RPSs) represent a circular approach to close the loop of consumption in which packaging can stay longer in the system to satisfy social needs. However, the implementation of reusable packaging is limited. Produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…These 15 archetypal models represent all of the variations of RPSs in the market until 2020. It has to be underlined that businesses within same archetypal models may be also different, as identified by Long et al [46]. These three archetypal models are part of a framework that includes a total of 15 archetypal models, and the insights of this research may only be generalised to those three archetypal models.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…These 15 archetypal models represent all of the variations of RPSs in the market until 2020. It has to be underlined that businesses within same archetypal models may be also different, as identified by Long et al [46]. These three archetypal models are part of a framework that includes a total of 15 archetypal models, and the insights of this research may only be generalised to those three archetypal models.…”
Section: Methodsmentioning
confidence: 92%
“…Notably, these three cases are examples of three different reusable packaging archetypal models ('archetypal model' refers to a group of businesses sharing similar characteristics). Long et al [46] identified 15 archetypal models based on the characteristics (i.e., ownership of the packaging, service types, service locations, target groups and delivery methods). These 15 archetypal models represent all of the variations of RPSs in the market until 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors highlight the importance of marketing strategies (Kunamaneni et al, 2019;Lialiuk et al, 2019;Muranko et al, 2020). Clear communication of system benefits and function is required to ensure the intended consumer behaviours are adopted (Lofthouse and Bhamra, 2006;Lofthouse et al, 2009;Long et al, 2020).…”
Section: Social Factorsmentioning
confidence: 99%
“…Logistics [6][7][8][9][10][11][12][13][14][15][16][17] Consumer acceptance [18 -22] Description of existing B2C reuse systems [23,24] [ 25 -32] Estimation of potential reductions in environmental impacts [33 -46] Design for reuse [47,48] Food safety [49 -54] Miscellaneous [55, 56] [5,57,58] The difference between the category "description of existing B2C reuse systems" and "estimation of potential reductions in environmental impacts" can be complex, since there are studies that combine elements of both.…”
Section: Subject Articles Reportsmentioning
confidence: 99%
“…Furthermore, the majority of the scientific articles and national reports focusses on the return-on-the-go business model, only seven articles and one report describe other business models [5,22,38,40,42,44,47,48].…”
Section: Figure 2 Studies That Explore the Potential Environmental Be...mentioning
confidence: 99%